KIDS Energy Density Functional and Mass–Radius Relation of Neutron Stars - Ahn, G.; Papakonstantinou, P. (HNPS Advances in Nuclear Physics, 2019)
Many efforts are made to determine the nuclear equation of state which governs the properties and evolution of neutron stars. Especially important is to constrain the parameters of the nuclear symmetry energy. In those efforts, nuclear energy density functional (EDF) theory has been a very useful tool, as it provides a unified framework for the description both of nuclei, which can be studied on Earth, and of infinite matter and its nuclear equation of state, which is a necessary input in the modelling of neutron stars. In the present study, a new nuclear EDF, the KIDS functional, is explored with a focus on the nuclear symmetry energy. The form of the functional allows us to vary at will the poorly constrained high-order derivatives of the symmetry energy and examine how the maximum possible mass of a neutron star is affected. Some tentative constraints on the skewness are presented, which will help guide further refinements. It is noteworthy that the pressure of neutron-rich matter is found strongly affected by skewness variations, both at low and high densities.